Influência do efeito prioritário no estabelecimento de duas espécies de macrófitas aquáticas. - Machado, Rafaela dos Santos (2024)
Species that arrive first at a site can impact the success of those that arrive later due to competition and changes in the environment, a process known as the “priority effect”. This study evaluates how the priority effect influences competition between two species native to South America, one highly invasive outside its area of origin (Alternanthera philoxeroides) and another with high invasive potential in other regions (Polygonum ferrugineum). This research tests the hypothesis that the negative effect on the growth and competitive ability of one of the species is greater when the other species is already established (priority effect). An experiment was carried out with five treatments: two treatments with each of the species planted a priori, one treatment with both planted simultaneously and two monocultures. From the biomass values obtained, the relative intensity of competition (ICR) and the relative growth rate (RGR) were calculated. For both species, the ICR values calculated for aboveground biomass, root biomass, total biomass and root biomass: above biomass ratio were higher in the presence of the priority effect. Congruent with these results, the RGR of the species was lower in the presence of the priority effect. This study shows that stochastic effects, such as the order of arrival of one of the species, can be decisive for the success of the other species under natural conditions.